PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), DAN RETURN ON ASSETS (ROA) TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN - Muhammad Yusuf; Suhendar Suhendar; Yoyo Sudaryo; Mohamad Arfiman Yosep; Omo Permana; Ardinal Djalil; Mohd Hassan Che Haat; Zikri Muhammad; Mohd Yusoff Yusliza; Jumadil Saputra (Universitas Insan Cendekia Mandiri, 2022)
This study aims to explain the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Assets (ROA) on Financial Distress. In this study, the method used is a quantitative method with a descriptive and verification approach. The type of data used is secondary data and data collection obtained through the company's official website and the Indonesia Stock Exchange (IDX) in the form of financial reports. Data analysis and data processing using the EViews 10 program. The results showed that partially Current Ratio (CR) had a significant effect on Financial Distress. Debt to Equity Ratio (DER) has no significant effect on Financial Distress. Return on Assets (ROA) has a significant effect on Financial Distress. And simultaneously Current Ratio (CR), Debt to Equity (DER), and Return on Assets (ROA) have a significant effect on Financial Distress Penelitian ini bertujuan untuk menjelaskan pengatuh Current Ratio (CR), Debt to Equity Ratio (DER), dan Return on Assets (ROA) terhadap Financial Distress. Dalam penelitian ini metode yang digunakan adalah metode kuantitatif dengan pendekatan deskriptif dan verifikatif. Jenis data yang digunakan ada data sekunder dan pengumpulan data yang didapat melalui web resmi perusahaan dan Bursa Efek Indonesia (BEI) berupa laporan keuangan. Analisis data dan pengolan data menggunakan program EViews 10. Hasil penelitian menunjukkan bahwa secara parsial Current Ratio (CR) berpengaruh signifikan terhadap Financial Distress. Debt to Equity Ratio (DER) tidak berpengaruh signifikan terhadap Financial Distress. Return On Assets (ROA) berpengaruh signifikan terhadap Financial Distress. Serta secara simultan Current Ratio (CR), Debt to Equity (DER), dan Return on Assets (ROA) berpengaruh signifikan terhadap Financial Distress.